The Taxation of Artificial Intelligence between New Taxes and Additional Incentives - Uricchio, Antonio Felice (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
The profound changes that accompany the history of humanity seem to depend largely on the unstoppable force of knowledge and innovation. The diffusion of robotics and artificial intelligence has had a significant impact on the processes of wealth production, with inevitable repercussions also on the labour market: today intelligent robots can carry out activities that were only human until recently. In this view, following the growing importance of the use of robots in modern society, the theme of the “robot tax” has assumed no small importance. The essay examines the various solutions imagined, evaluating the proposals to recognize the tax subjectivity of robots or to define the taxable case, assuming, depending on the case, as a prerequisite for the tax, the ability to accumulate data and knowledge, the property value of the robot-good or the greater profits deriving from the activity carried out using it.